A genome-wide association analysis: m6A-SNP related to the onset of oral ulcers - Wu, Zhuoxuan; Lin, Weimin; Yuan, Quan; Lyu, Mingyue (Frontiers in Immunology, 2022)
Oral ulcers are one of the most common inflammatory diseases on oral mucosa that have definite impacts on patients. Studies have shown that N6-methyladenosine (m6A) RNA transcription modification may be involved in the development of various inflammatory progresses, and whether the pathogenesis of oral ulcers is related to m6A is unclear. This study aims to identify how m6A related single nucleotide polymorphisms (m6A-SNPs) affect oral ulcers. The UKBB dataset containing 10,599,054 SNPs was obtained from the GWAS database using "oral ulcer "as keyword and compared with the M6AVar database containing 13,703 m6A-SNPs.With 7,490 m6A-SNPs associated with oral ulcer identified, HaploReg and RegulomeDB were used for further functional validation and differential gene analysis was performed using the GEO database dataset GSE37265. A total of 7490 m6A-SNPs were detected in this study, 11 of which were related to oral ulcers (p<5E-08), and all of these SNPs showed eQTL signals. The SNP rs11266744 (p=2.00E-27) may regulate the expression of the local gene CCRL2, thereby participating in the pathogenesis of oral ulcers. In summary, by analyzing genome-wide association studies, this study showed that m6A modification may be involved in the pathogenesis of oral ulcers and CCRL2 may be the specific mechanism.